Health hazards resulting from occupational exposure to enfluran - overview of tests and analysis of admissible concentration values - Małgorzata Kupczewska-Dobecka (Nofer Institute of Occupational Medicine, 2022)
The aim of this work is to analyze the health hazards of enflurane exposure and to analyze the occupational exposure limits (OEL). The method of obtaining evidence based on a review of online databases of scientific journals was used. Enflurane is an inhalation anesthetic. Malignant hyperthermia, seizures, arrhythmias, respiratory depression and hypotension have been observed in patients. Occupational exposure to enflurane may occur in healthcare professionals. The target organ for enflurane is the central nervous system with a critical consequence of deterioration in psychomotor performance. In studies on volunteers recruited from the medical staff of operating rooms exposed to enflurane, a significant deterioration in the results of the Simple Reaction Time Test was shown. World experts' groups assume that the LOAEC (lowest observed adverse effect concentration) value for the deterioration of psychomotor test results is 5-10% of the MAC value (minimal anesthetic concentration), i.e., 6342-12 684 mg/m3. Assessment of the nephrotoxic potential of enflurane has shown that it is unlikely to occur because biotransformation of enflurane in humans results in a low peak serum fluoride concentration of 15 μmol/l. Early reports about liver damage in patients were not be supported. Occupational exposure epidemiological studies have raised concerns about the effects of anesthetic gas mixtures on the abortion rate or on fetal development and birth defects in children, but none of these studies specifically determined the type and concentration of anesthetic gases used. The carcinogenicity and mutagenicity studies were negative. Occupational exposure to enflurane is not monitored in Poland, as no standard value has been established for it in the air of the working environment. It is necessary to quickly introduce this anesthetic along with the applicable limit value to the OEL list. Med Pr. 2022;73(1):51-69